Transformasi Sistem Pendidikan Pesantren Dari Pesantren Salaf Ke Terpadu: Studi Kasus Pondok Pesantren Salafiy Terpadu Ar-Risalah Lirboyo - Humaidi, Anis (Didaktika Religia, 2013)
This article explores interesting phenomena occurring at Pondok Pesantren Lirboyo, that is transformation system. Even though it is popular with salaf tradition, Pondok Pesantren Salafiy Terpadu Ar-Risalah is successfully integrating salaf education system and modern system. The new generation of the Pondok are not always satisfied with what was established with the founding fathers of the Pondok due to the change of reality. Therefore, transformation happens. This can be seen in Pondok Pesantren Salafiy Terpadu Ar-Risalah Lirboyo, which integrates salaf tradition and modern system.